3-Cyclohexyl-4-(3-methyl-3-phenylcyclobutyl)-1,3-thiazole-2(3H)-thione - Kirilmis, C; Koca, M; Arici, C; Heinemann, FW; Ahmedzade, M (Int Union Crystallography, 2005)
The cyclohexyl ring of the title compound, C20H25NS2, has a chair conformation. The dihedral angle between the thiazole and phenyl rings is 89.70 ( 2) degrees. The crystal structure involves two weak intramolecular C - H center dot center dot center dot S hydrogen-bond contacts.